COMPETITION LAW AND POLICY FOR THE INTERNET OF THINGS - Nikolic, Igor (Pravni zapisi, 2022)
The Internet of Things (IoT) brings mobile internet connectivity to many different sectors of the economy. 5G standard is expected to play a key role in fostering seamless connectivity between devices. However, it also requires licensing patents essential for 5G standards to a diverse group of companies. How to effectively license essential patents in IoT has been the central question in recent policy debates before the European Commission. Competition law has often been invoked as a solution to either directly regulate certain licensing practices or to take a step back and enable the industry to collectively agree on certain licensing solutions. The article analyses three situations where the role of competition law was discussed: i) refusal to license patents to different levels of the production chain; ii) collective price-setting of a standard and iii) collective licensing of patents. The article examines each situation and discusses the appropriate role of competition law in fostering efficient licensing of essential patents in the IoT.